The Chicken Embryo: An Old but Promising Model for In Vivo Preclinical Research - Annachiara Sarnella; Ylenia Ferrara; Cristina Terlizzi; Sandra Albanese; Serena Monti; Luca Licenziato; Marcello Mancini (Biomedicines)
The chicken embryo has emerged as a valuable model for preclinical studies due to its unique combination of accessibility, affordability, and relevance to human biology. Its rapid development, external growth environment, and clear structural visibility offer distinct advantages over traditional mammalian models. These features facilitate the study of real-time biological processes, including tissue development, tumor growth, angiogenesis, and drug delivery, using various imaging modalities, such as optical imaging, magnetic resonance imaging, positron emission tomography, computed tomography, and ultrasound. The chicken embryo model also minimizes ethical concerns compared to mammalian models, as it allows for early-stage research without the complexity of a fully developed animal. Moreover, its ability to integrate human tumor cells into xenograft models provides a reliable platform for cancer research, enabling high-throughput screening of therapeutic interventions and tracking molecular dynamics in vivo. Advances in molecular imaging techniques further enhance the resolution and depth of data obtained from these studies, offering insights into cellular and molecular mechanisms underlying disease. Given its versatility, cost-effectiveness, and translational potential, the chicken embryo represents a promising tool for advancing preclinical research, particularly in drug development, cancer biology, and regenerative medicine.